Food Security and Livelihoods of Small-Scale Producers - Searchinger, Tim; Brown, Molly; Campbell, Bruce M.; Carter, Rebecca; Thornton, Philip K. (Global Center on Adaptation, 2019)
This report focuses on making the case for climate adaptation, providing specific insights and recommendations in key sectors: food security, the natural environment, water, cities and urban areas, infrastructure, disaster risk management, and finance. It is designed to inspire action among decision-makers, including heads of state and government officials, mayors, business executives, investors, and community leaders.